Treatment Approaches for Atypical CIDP - Menon, Deepak; Katzberg, Hans Dieter; Bril, Vera (Frontiers in Neurology, 2021)
The variants of chronic inflammatory demyelinating polyneuropathy (CIDP) differ not just in their clinical, pathological and electrophysiological characteristics, but often in their indifferent response to conventional immunosuppressive agents which are effective in typical CIDP. High quality evidence is lacking as far as the management of these atypical variants is concerned. In this review, we summarize the treatment approaches to each of these CIDP variants based on existing data. Distal acquired demyelinating symmetric polyneuropathy (DADS) has the phenotype of a symmetric, demyelinating sensory, length-dependent polyneuropathy and is frequently associated with paraproteinemia and anti myelin associated glycoprotein (MAG) antibodies. While the management of idiopathic DADS (DADS-I) is the same as CIDP, DADS-M responds suboptimally and has a favorable response to rituximab. Multifocal acquired demyelinating sensory and motor neuropathy (MADSAM) manifests as a chronic progressive demyelinating mononeuropathy multiplex which can evolve to a confluent pattern indistinguishable from CIDP. Evidence favors treating MADSAM with conventional immunomodulatory therapy (IMT), but this disorder responds less favorably than CIDP. Some patients present with purely sensory symptoms, known as pure sensory CIDP or chronic inflammatory sensory polyradiculoneuropathy (CISP), the latter localizing to a pre-ganglionic pathology. Both respond well to first line IMT, particularly to intravenous immunoglobulin (IVIG), but patients relapse without maintenance therapy. Pure motor CIDP resembles multifocal motor neuropathy with conduction block (MMNCB), but the previously reported worsening status after steroid treatment was not reproduced in recent studies, and IVIG remains the first-line therapy. Some focal forms of CIDP defy exact classification, but respond well to first-line IMT including IVIG. Overall, atypical CIDP responds to treatment with first-line IMT, but has a suboptimal response compared to CIDP. There is evidence for effectiveness with agents such as rituximab, especially in DADS-M, and this medication can also be used in cases refractory to conventional IMTs. Rituximab is also effective in CIDP with IgG4 antibodies which has distinct clinical features and is mostly refractory to first-line IMT.